2017
DOI: 10.7739/jkafn.2017.24.4.265
|View full text |Cite
|
Sign up to set email alerts
|

An Action Research on Flipped Learning for Fundamental Nursing Practice Courses

Abstract: This study was conducted to design and implement a fundamental nursing practice based on flipped learning and to examine the effects. Methods: Participants were 57 students who were taking the fundamental nursing practice course at D university in N city. The study included processes of instructional design, action/effects and reflection. Data were analyzed using paired t-test with the SPSS/WIN 23.0. Results: In the instructional design stage, the class consisted of 3 parts: outside class (pre-learning), insid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 13 publications
6
13
0
1
Order By: Relevance
“…Evaluation of the differences between pre-and postintervention scores on the SECC This study showed that our ipped classroom teaching approach has a potential to create positive learning outcomes in terms of clinical skills, communication, and teamwork capabilities, as well as the competencies of critical thinking, caring, work ethic, and accountability. Our ndings were partially consistent with those of Jang and Hong [31] (critical thinking), Durmaz et al [17] (admission skills), Kim and Kim [23] (fundamental nursing practice course), Gerdsprasert et al [19] (intrapartum care competency), McMullan et al [24] (drug calculation ability), Bloom eld et al [16] (handwashing skills), Sassen et al [32] (shared decision making), and Kaveevivitchai et al [21] (vital signs assessment skill).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Evaluation of the differences between pre-and postintervention scores on the SECC This study showed that our ipped classroom teaching approach has a potential to create positive learning outcomes in terms of clinical skills, communication, and teamwork capabilities, as well as the competencies of critical thinking, caring, work ethic, and accountability. Our ndings were partially consistent with those of Jang and Hong [31] (critical thinking), Durmaz et al [17] (admission skills), Kim and Kim [23] (fundamental nursing practice course), Gerdsprasert et al [19] (intrapartum care competency), McMullan et al [24] (drug calculation ability), Bloom eld et al [16] (handwashing skills), Sassen et al [32] (shared decision making), and Kaveevivitchai et al [21] (vital signs assessment skill).…”
Section: Discussionsupporting
confidence: 86%
“…In the digital era, instructors or teachers often combine computer-mediated technology and face-to-face in-class activities to enhance students' engagement in pre-class work, inclass learning, and post-class assignments, as well as to help students achieve their goals during the ipped classroom processing period [8,12,13]. Several studies have shown that students prefer a hybrid course structure and their learning outcomes can improve in knowledge, decision-making skills, satisfaction, thinking abilities, and re ections concerning clinical practice [16,17,18,19,20,21,22,23,24,25,26]. Most of these studies also demonstrated the mastery learning behavior suggested by Bloom [27], which posits that learning activities applied in class, such as professional knowledge, relevant skills, and scholarly inquiry, might transfer to real clinical practice [8].…”
Section: Flipped Classrooms and Hybrid Teaching Methodsmentioning
confidence: 99%
“…Evaluation of the differences between pre-and post-intervention scores on the SECC This study showed that our flipped classroom teaching approach has a potential to create positive learning outcomes in terms of clinical skills, communication, and teamwork capabilities, as well as the competencies of critical thinking, caring, work ethic, and accountability. Our findings were partially consistent with those of Jang and Hong [31] (critical thinking), Durmaz et al [17] (admission skills), Kim and Kim [23] (fundamental nursing practice course), Gerdsprasert et al [19] (intrapartum care competency), McMullan et al [24] (drug calculation ability), Bloomfield et al [16] (handwashing skills), Sassen et al [32] (shared decision making), and Kaveevivitchai et al [21] (vital signs assessment skill).…”
Section: Discussionsupporting
confidence: 88%
“…Our findings were partially consistent with those of Jang and Hong [31] (critical thinking), Durmaz et al [17] (admission skills), Kim and Kim [23] (fundamental nursing practice course), Gerdsprasert et al [19] (intrapartum care competency), McMullan et al [24] (drug calculation ability), Bloomfield et al…”
Section: Evaluation Of the Intervention's Effect On Seccsupporting
confidence: 89%